1996
DOI: 10.1177/000992289603500602
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Outcome of Infants with Viral Meningitis in the First Three Months of Life

Abstract: We prospectively evaluated the neurodevelopmental outcome of infants with documented viral meningitis to determine (1) whether deficits in physical growth, development, speech and language, hearing, or intelligence occur; and (2) if so, at what age these deficits can be detected. Sixteen infants with documented enteroviral meningitis under the age of 90 days and a control group of 13 patients matched for age, race, sex, and socioeconomic status were followed up prospectively for 3 years with annual evaluations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…[35][36][37][38] authors have documented language delays in infants who have had EV meningitis before 3 months of age. 36,38 PCR diagnosis followed by molecular typing could clarify which serotypes are most likely to produce CNS involvement and which infants, if any, may be at risk for neurodevelopmental delay. 39 EV-positive infants were significantly less likely to have SBI than were EV-negative infants; however, all enterovirus-infected infants were hospitalized and received broad-spectrum intravenous antibiotics, most for a minimum of 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38] authors have documented language delays in infants who have had EV meningitis before 3 months of age. 36,38 PCR diagnosis followed by molecular typing could clarify which serotypes are most likely to produce CNS involvement and which infants, if any, may be at risk for neurodevelopmental delay. 39 EV-positive infants were significantly less likely to have SBI than were EV-negative infants; however, all enterovirus-infected infants were hospitalized and received broad-spectrum intravenous antibiotics, most for a minimum of 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of the pattern and stability of hearing loss after bacterial meningitis, Brookhouser et al [1988] reported that hearing loss was stable in 86% of 64 children with postmeningitic hearing loss, and that the losses were most commonly bilateral and profound. In a follow-up study of viral meningitis, Baker et al [1996] evaluated the neurodevelopmental outcome of 16 infants with documented viral meningitis. By the three-year follow-up, they found no hearing losses or deficits in growth, development, articulation, Bayley Scales of Infant Development, or expressive language, but did document subtle but significant deficits in language function.…”
Section: Meningitismentioning
confidence: 99%
“…Language development is also arguably one of the most rapid aspects of development, and shows great variability between children (Bates, Dale, & Thal, 1995;Fenson et al, 2000;Fenson, Dale, Reznick, & Bates, 1994), as well as being sensitive to a number of negative factors that are more common in this setting, including HIV infection, cerebral malaria, meningitis, and other causes of brain injury and dysfunction (Baker, Kummer, Schultz, & Ho, 1996;Bates et al, 1997;Brouwers et al, 2001;Davis et al, 1997;McNeilly, 2005;Wolters, Brouwers, Civitello, & Moss, 1997). Its study therefore has become in recent years an essential part of studies of child development outcomes following exposures and interventions in the prenatal period and infancy (A. Abubakar, Van Baar, Prado et al, 2010;Stoltzfus et al, 2001).…”
Section: Introductionmentioning
confidence: 99%